IL LASCITO DEL CARDINALE. UN RIPOSTIGLIO DI ANTONINIANI DALL’ITALIA SETENTRIONALE (?) - Michele Asolati (Journal of Ancient History and Archaeology, 2020)
This contribution concerns a nucleus of coins donated to the Republic of Venice by the Venetian Cardinal Giovan Battista Zen by 1501. Arrived at the Libreria Marciana and then unexpectedly divided between the collections of the Museo Archeologico Nazionale in Venice and the Museo Correr in Venice, this collection is now largely identifiable thanks to the archival ducumentation at the Biblioteca Marciana in Venice. The characteristics that these coins have in common make it possible a well-founded assumption that the entire nucleus donated by Zen was a hoard of denarii and antoniniani, which ends with issues of the Gallienic age. Reconstructed in this way, the hoard is comparable with many other Italian treasures, mainly from central and northern Italy, probably hoarded as a result of the continuous devaluation of the antoninianus in the '60s of the third century. These comparisons allow us to locate within these areas the possible site find of the hoard, since these are also the context in which the pastoral activity of the Cardinal took place.